Method for Managing Human Resources Better in Digital Marketing - Surya Astitiani, Ni Luh Putu; widnyani, Ni made; Darmayanti, Ni Luh; Wahyuningsih, Luh Gde Nita Sri; Carla Rettobjaan, Vitalia Fina (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Modern business trends are becoming more diverse as technology, particularly digital marketing, develops. The idea behind and use of digital marketing is an endeavor to increase sales of goods from a brand. Every human resource in the organization must be able to master this competency because it is the key to the growth of the business overall. Human resources must come up with plans to increase employee proficiency in digital marketing. The goal of the approach is to improve marketers' understanding of potential customers, their communication skills, and their capacity to identify the best marketing mix for each target market. The most effective digital marketers are those who have a clear understanding of how each campaign supports the goals of the offering. Digital marketers can use their free or paid media to produce broader campaigns depending on the objectives of their marketing plan. In order to increase the company's human resources' proficiency in digital marketing, this study focuses on the deployment of efficient training programs. A review of the literature using descriptive qualitative processing techniques was the research methodology used in this study.